Combination of myeloproliferative neoplasm driver gene activation with mutations of splice factor or epigenetic modifier genes increases risk of rapid blastic progression. (1st February 2021) - Bartels, Stephan; Vogtmann, Julia; Schipper, Elisa; Büsche, Guntram; Schlue, Jerome; Lehmann, Ulrich; Kreipe, Hans
Abstract: Objectives: Myeloproliferative neoplasms (MPN) comprising polycythemia vera (PV), essential thrombocythemia (ET) and primary myelofibrosis (PMF) follow a bi‐phasic course of disease with fibrotic and/or blastic progression. At presentation in the chronic phase, currently there are only insufficient tools to predict the risk of progression in individual cases. Methods: In this study, chronic phase MPN (16 PMF, 11 PV, and 11 MPN unclassified) with blastic transformation during course of disease (n = 38, median follow‐up 5.3 years) were analyzed by high‐throughput sequencing. MPN cases with a comparable follow‐up period and without evidence of blast increase served as control (n = 63, median follow‐up 5.8 years). Results: Frequent ARCH/CHIP‐associated mutations ( TET2, ASXL1, DNMT3A ) found at presentation were not significantly associated with blastic transformation. By contrast, mutations of SRSF2, U2AF1, and IDH1/2 at first presentation were frequently observed in the progression cohort (13/38, 34.2%) and were completely missing in the control group without blast transformation during follow‐up ( P = .0007 for SRSF2 ; P = .0063 for U2AF1 and IDH1/2 ). Conclusion: Unlike frequent ARCH/CHIP alterations ( TET2, ASXL1, DNMT3A ), mutations in SRSF2, IDH1/2, and U2AF1 when manifest already at first presentation provide an independent risk factor for rapid blast transformation of MPN.